1983
DOI: 10.1017/s0003356100040034
|View full text |Cite
|
Sign up to set email alerts
|

The energy and nitrogen metabolism and performance of pigs infected with Oesophagostomum dentatum

Abstract: The effect of Oesophagostomum dentatum on the performance of growing pigs over the live-weight range 20 to 80 kg was investigated. Fourteen individually-penned pigs in Experiment 1 and 16 group-penned but individually fed pigs in Experiment 2 were orally dosed once with 80 000 or 20 000 larvae respectively at about 18 kg live weight. Worm-free but otherwise similar pigs served as controls. Three energy and nitrogen balance studies were undertaken in two open-circuit calorimeters on four infected gilts and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…The duration of the prepatent period in our study did not dier between the two species or between isolates and was also independent of the type of infection, i.e., monoinfection or combined two-species infection, and their anthelmintic resistance status. However, our observations correspond to other, more recent recordings of prepatent periods of 18±21 days for O. dentatum (Pattison et al 1980;Stewart et al 1983) and of 20 days for mixed infections (Tas 1968;Bjùrn et al 1990). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The duration of the prepatent period in our study did not dier between the two species or between isolates and was also independent of the type of infection, i.e., monoinfection or combined two-species infection, and their anthelmintic resistance status. However, our observations correspond to other, more recent recordings of prepatent periods of 18±21 days for O. dentatum (Pattison et al 1980;Stewart et al 1983) and of 20 days for mixed infections (Tas 1968;Bjùrn et al 1990). …”
Section: Discussionsupporting
confidence: 93%
“…In contrast, A. Daugschies (personal communication) found prepatent periods of 17±18 days in an O. dentatum isolate, regardless of the dose level, which ranged from 35,000 to 100,000 L 3 . Stewart et al (1983) found a prepatent period of 19±26 days when pigs were infected with 80,000 L 3 of O. dentatum.…”
Section: Discussionmentioning
confidence: 89%